2022
DOI: 10.1186/s12911-022-01844-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of clinical-guideline-based mobile application and its effect on head CT scan utilization in neurology and neurosurgery departments

Abstract: Background There is little evidence regarding the adoption and intention of using mobile apps by health care professionals (HCP) and the effectiveness of using mobile apps among physicians is still unclear. To address this challenge, the current study seeks two objectives: developing and implementing a head CT scan appropriateness criteria mobile app (HAC app), and investigating the effect of HAC app on CT scan order. Methods A one arm interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Sixteen medical interns evaluated the quality of the HAC app using the MARS tool from March to June 2021. HAC app was developed during the former study with the collaboration of experts at KAUMS to assist medical interns and residents in head CT scan ordering [8]. It enables end-users to seek appropriate CT scans based on diseases, signs & symptoms, and modalities, e.g., CT, CTA, and MRI (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen medical interns evaluated the quality of the HAC app using the MARS tool from March to June 2021. HAC app was developed during the former study with the collaboration of experts at KAUMS to assist medical interns and residents in head CT scan ordering [8]. It enables end-users to seek appropriate CT scans based on diseases, signs & symptoms, and modalities, e.g., CT, CTA, and MRI (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, previous literature debated HCPs do not frequently use CDSS due to poor usability [5]. The adoption of CDSSs depends on the provision of an understandable justification of the clinical decision-making process, fully interaction to respond to physicians' questions and to provide feedback and interpretation [6]. Evidence suggested that clinicians require help for ABG tests interpretation, a challenging task due to facing physicians with six values [7].…”
Section: Introductionmentioning
confidence: 99%